PENGARUH KOMPENSASI DAN PENGENDALIAN INTERNAL TERHADAP KINERJA KARYAWAN PADA PT AUTOSERVICE DELTA NIAGA BANJARMASIN - Ruslinda Agustina; Rizki Amalia Afriana (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2020)
Abstract, The purpose of this research is to empirically prove the effect of compensation and internal control on employee performance at PT Autoservice Delta Niaga Banjarmasin. The research method used is quantitative descriptive method. The author distributes the questionnaire with the intended analysis unit is the employee of the company that the respondent is assigned to. The number of research samples were 35 employees. The statistical test tool uses the SPSS version 16 program. The results showed that compensation affected the performance of employees with a significant value of 0,000. Internal control affects employee performance with a significant value of 0.040. This shows that if compensation and high internal control can improve the performance of employees.